1988
DOI: 10.1111/j.1432-1033.1988.tb13802.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an anti‐thrombospondin monoclonal antibody (P8) that inhibits human blood platelet functions

Abstract: Stimulated human blood platelets release thrombospondin, an α‐granule glycoprotein of 450 kDa. The aim of this work was to characterize an anti‐thrombospondin monoclonal antibody (P8) in order to study the role of thrombospondin in platelet functions. The presence of thrombospondin receptor sites on resting and thrombin‐stimulated platelets of three Glanzmann's thrombasthenia patients and normal donors was investigated using the P8 monoclonal antibody. Monoclonal antibody P8 was extensively characterized using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 56 publications
3
36
0
Order By: Relevance
“…This resulted in the formation of smaller aggregates, as we previously observed with mAb MAIL 11 In agreement with previous work that demonstrated the role of endogenous or exogenously added TSP in platelet aggregation, 10 - 43 we found that higher concentrations of ADP (10 /miol/L) or thrombin (0.2 U/mL) could overcome the inhibitory effect of the recombinant proteins. These results underline the important role played by TSP in promoting platelet aggregation at low concentrations of stimulating agents.…”
Section: Discussionsupporting
confidence: 79%
“…This resulted in the formation of smaller aggregates, as we previously observed with mAb MAIL 11 In agreement with previous work that demonstrated the role of endogenous or exogenously added TSP in platelet aggregation, 10 - 43 we found that higher concentrations of ADP (10 /miol/L) or thrombin (0.2 U/mL) could overcome the inhibitory effect of the recombinant proteins. These results underline the important role played by TSP in promoting platelet aggregation at low concentrations of stimulating agents.…”
Section: Discussionsupporting
confidence: 79%
“…12D). This latter model may appear controversial because platelets from patients with Glanzmann's thrombastenia, which lack GPIIbIIIa, have been shown to express normal levels of TSP at the cell surface upon thrombin activation, with no aggregation detected in an aggregometer (23,47). However, this apparent contradiction with our model may rather arise from the facts that (i) micro-aggregates of Ͻ10 platelets observed in one Glanzmann's thrombastenia patient by phase contrast microscopy may not be detected by aggregometry (48) and (ii) electron microscopy studies revealed that upon thrombin activation, TSP was not distributed normally on the platelet surface of one Glanzmann's thrombastenia patient, with decreased size and number of TSP clusters (49).…”
Section: Effect Of the Addition Of Tsp On Aggregation Efficiency Of Fmentioning
confidence: 99%
“…Cell extracts in RIPA buffer were prepared, and equal amounts of proteins were resolved in SDS/PAGE, transferred, and evaluated for c-Src and FAK expression and activity with the indicated antibodies as previously described (4). For coimmunoprecipitations, equivalent amounts of cell lysates were incubated for 2 h at 4°C with antibodies to c-Src coupled to protein G-Sepharose as described previously (32). Immunoprecipitates were extensively washed, and the eluted precipitates were resolved by SDS/7% PAGE, transferred, and probed with the appropriate antibodies.…”
Section: Methodsmentioning
confidence: 99%